IMPACT OF SINGLE AND DOUBLE ZINCATING TREATMENT ON ADHESION OF ELECTRODEPOSITED NICKEL COATING ON ALUMINIUM ALLOY 7075 - Othman, I.S.; Starink, M.J.; Wang, S.C. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
The purpose of this investigation is to explore the relationship between various zincating treatments and coating adhesion. A modification on the conventional single zincating process has been made by extending the duration, with an objective to enhance the non-homogeneous deposition of zinc particles on the aluminium alloy 7075 (AA7075) substrate. To compare the impact of various zincating treatments on the coating adhesion, a double zincating process at various durations were also applied in this study. A scanning electron microscopy (SEM), atomic force microscopy (AFM) and energy dispersive analysis of x-rays (EDX) were used to characterize the microstructural changes and composition of AA7075 during various zincating treatments at various durations. A scratch tester was used to investigate the coating adhesion of nickel deposits. A strong relationship between zincating duration and surface morphology of the zincated substrate has been observed in SEM results. The adhesion between the coating and substrate was improved at a longer single zincating duration, compared to conventional single and double zincating process. This finding suggests that the homogenous distribution and good coverage of zinc particles on the substrate have contributed to the improvement of the coating adhesion.